2009
DOI: 10.1159/000239796
|View full text |Cite
|
Sign up to set email alerts
|

Differential Prognostic Impact of uPA and PAI-1 in Colon and Rectal Cancer

Abstract: Background and Objectives: Degradation of extracellular matrix is important for tumour growth and invasion, which in part is regulated by the plasminogen activation system. The aim of the study was to evaluate the protein expression of urokinase plasminogen activator (uPA) and plasminogen-activating inhibitor-1 (PAI-1) in plasma, tumour-free mucosa and tumour tissue regarding their prognostic value in colon and rectal cancer. Methods: Patients (n = 221) undergoing surgery for colorectal cancer were prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
1
22
0
3
Order By: Relevance
“…6,7 There is evidence that plasma PAI-1 is correlated closely with rectal cancer metastasis, and tumor tissue PAI-1 is associated with the histopathology and outcome of rectal cancer. 8,9 Whether PAI-1 may serve as a target in antitumor therapy of CRC remains unclear.…”
mentioning
confidence: 99%
“…6,7 There is evidence that plasma PAI-1 is correlated closely with rectal cancer metastasis, and tumor tissue PAI-1 is associated with the histopathology and outcome of rectal cancer. 8,9 Whether PAI-1 may serve as a target in antitumor therapy of CRC remains unclear.…”
mentioning
confidence: 99%
“…[14] Degradation of extracellular matrix is important for tumour growth and invasion, which in part is regulated by the plasminogen activation system. [15,16,17] Therefore, an elevated plasma D-dimer level indicates activation of both coagulation and fibrinolysis. [8] The present study showed a significant difference between D-dimer levels in breast carcinoma patients pre-operatively and post-operatively as well as significantly higher levels in cases as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Показано, что uPA участвует в формировании сети новых сосудов в опухолях толстой кишки [38]. Также имеются указания на то, что наличие положительного окрашивания или высокая концентра-ция PAI-1 или uPA при количественном определении служат факторами неблагоприятного прогноза [26,33,39,40]. В одной из ранних работ установлено [41], что наиболее значимым прогностическим фактором при РТК является отношение концентрации uPA в опухоли к концентрации tPA в окружающей слизистой оболочке толстой кишки.…”
Section: актуальные вопросы онкологииunclassified
“…Поскольку в литературе приведены данные о том, что определенное влияние на выживаемость больных РТК может оказывать содержание компонентов системы ак-тивации плазминогена не только в опухоли, но и в окру-жающей неизмененной слизистой оболочке [40], или со-отношение различных показателей в опухоли и слизистой [41], нами проведен соответствующий анализ, в котором в качестве пороговых значений использовали медианные уровни соответствующих белков в неизмененной слизи-стой оболочке. Достоверного влияния на выживаемость ни для одного из проанализированных параметров не обнаружено, однако как в общей группе пациентов, так и у больных с III стадией установлена выраженная тенден-ция к ухудшению выживаемости при низком уровне uPA (менее 0,24 нг/мг) в неизмененной слизистой оболочке.…”
Section: актуальные вопросы онкологииunclassified
See 1 more Smart Citation